2017
DOI: 10.1093/toxsci/kfx147
|View full text |Cite
|
Sign up to set email alerts
|

Editor’s Highlight: PPARβ/δ and PPARγ Inhibit Melanoma Tumorigenicity by Modulating Inflammation and Apoptosis

Abstract: Skin tumorigenesis results from DNA damage, increased inflammation, and evasion of apoptosis. The peroxisome proliferator-activated receptors (PPARs) can modulate these mechanisms in non-melanoma skin cancer. However, limited data exists regarding the role of PPARs in melanoma. This study examined the effect of proliferator-activated receptor-β/δ (PPARβ/δ) and PPARγ on cell proliferation, anchorage-dependent clonogenicity, and ectopic xenografts in the UACC903 human melanoma cell line. Stable overexpression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…PPARβ/δ was previously shown to be expressed in melanocytes [ 12 ], suggesting a potential physiological role in melanocyte activity and function. Although the activation of PPARβ/δ has no impact on melanocyte proliferation [ 12 ], it significantly inhibits the proliferation of melanoma cells, prevents anchorage-dependent clonogenicity and attenuates ectopic xenograft tumorigenicity [ 13 ]. On the contrary, shRNA-mediated knockdown of PPARβ/δ in a highly malignant mouse melanoma cell line B16-F10 demonstrated reduced lung metastasis and tumour burden [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…PPARβ/δ was previously shown to be expressed in melanocytes [ 12 ], suggesting a potential physiological role in melanocyte activity and function. Although the activation of PPARβ/δ has no impact on melanocyte proliferation [ 12 ], it significantly inhibits the proliferation of melanoma cells, prevents anchorage-dependent clonogenicity and attenuates ectopic xenograft tumorigenicity [ 13 ]. On the contrary, shRNA-mediated knockdown of PPARβ/δ in a highly malignant mouse melanoma cell line B16-F10 demonstrated reduced lung metastasis and tumour burden [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This inhibition of cell proliferation by ligand activation of PPARβ/δ with either GW0742 or GW501516 was also found in both mouse and human melanoma cell lines and mediated by repression of Wilm's tumor suppressor 1 (WT1) that may, in turn, regulate expression of NESTIN and ZYXIN . These findings are of interest to note because ligand activation of PPARβ/δ with GW0742 and/or overexpression of PPARβ/δ inhibited the growth of ectopic xenografts derived from a human melanoma cell causing a block in cell proliferation at the G2/M phase of the cell cycle and induction of apoptosis as compared to controls . Moreover, because the melanoma cell line used for two of these studies was UACC903, which expresses mutant PTEN and an active AKT3, these results demonstrate that ligand activation and/or overexpression of PPARβ/δ are capable of preventing the negative effects of mutant PTEN and active AKT3, and possibly other mutations known to exist in this melanoma cell line .…”
Section: Pparβ/δ‐dependent Regulation Of Melanomamentioning
confidence: 69%
“…72 Because the latter study applied topical PPARβ/δ ligands postirradiation, the results from this study controlled for the sunscreen effect and provide a better degree of clarity than the former study 68 cell proliferation at the G2/M phase of the cell cycle and induction of apoptosis as compared to controls. 43 Moreover, because the melanoma cell line used for two of these studies 43,73 was UACC903, which expresses mutant PTEN and an active AKT3, these results demonstrate that ligand activation and/or overexpression of PPARβ/ δ are capable of preventing the negative effects of mutant PTEN and active AKT3, and possibly other mutations known to exist in this melanoma cell line. 44,75,76 Consistent with these studies, genetic ablation and pharmacological inhibition of PPARβ/δ demonstrated that PPARβ/δ inhibited epithelial-mesenchymal transition, migration, adhesion, and invasion of a mouse melanoma cell line and that PPARβ/δ prevented metastasis in a syngeneic mouse model of melanoma.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Indeed, FAs can bind and activate specific nuclear receptors, i.e., PPARs, thus controlling the expression of genes involved in lipid homeostasis, oxidative stress, and inflammation (59,60). Unfortunately, poor knowledge exists on this matter as the only evidence for a role of lipid signaling in melanoma biology comes from two recent papers in which the authors independently remarked an anti-tumor effect of PPARβ/δ and PPARγ in melanoma progression and metastasis (61,62).…”
Section: Metabolic Pathways In Melanomamentioning
confidence: 99%